2015
DOI: 10.3109/13880209.2014.970287
|View full text |Cite
|
Sign up to set email alerts
|

Stepwise high-throughput virtual screening of Rho kinase inhibitors from natural product library and potential therapeutics for pulmonary hypertension

Abstract: (2015) Stepwise high-throughput virtual screening of Rho kinase inhibitors from natural product library and potential therapeutics for pulmonary hypertension, Pharmaceutical Biology, 53:8, 1201-1206, DOI: 10.3109/13880209.2014 ORIGINAL ARTICLEStepwise high-throughput virtual screening of Rho kinase inhibitors from natural product library and potential therapeutics for pulmonary hypertension Hao Su, Ji Yan, Jian Xu, Xi-Zhen Fan, Xian-Lin Sun, and Kang-Yu Chen Department of Cardiology, Anhui Provincial Hospi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 29 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Several potent and selective ROCK inhibitors identified by modern drug discovery techniques are undergoing clinical trials for the treatment of multiple diseases 109,110 . Nevertheless, the structural diversity between these synthetic ROCK inhibitors is an issue which can hopefully be overcome with the discovery of natural products with moderate to potent ROCK inhibitory action 111,112 . These newly identified compounds may provide new leads for the development of improved, safer, and more effective ROCK inhibitors for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Several potent and selective ROCK inhibitors identified by modern drug discovery techniques are undergoing clinical trials for the treatment of multiple diseases 109,110 . Nevertheless, the structural diversity between these synthetic ROCK inhibitors is an issue which can hopefully be overcome with the discovery of natural products with moderate to potent ROCK inhibitory action 111,112 . These newly identified compounds may provide new leads for the development of improved, safer, and more effective ROCK inhibitors for the treatment of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Lanostane triterpenoids were found to have the most potent activities. In another study, Su et al virtually screened a natural product library and found phloretin and baicalein to inhibit Rho-kinase [81]. Phloretin is a dihydrochalcone found in apple and pears [82].…”
Section: Uveal Melanomamentioning
confidence: 99%